2019
DOI: 10.1039/c8nh00174j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide and carbon dots as broad-spectrum antimicrobial agents – a minireview

Abstract: Complex antibacterial mechanisms of graphene oxide and carbon dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
157
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(170 citation statements)
references
References 157 publications
1
157
0
Order By: Relevance
“…The factors influence to antibacterial effect come the medium culture condition (Mueller-Hinton Broth) or the purity of GO [55]. In contrast, other reports showed that GO had a bactericidal effect [10,56]. Previously, a three-step antibacterial mechanism of graphene-based materials was proposed: initial cell deposition, membrane stress caused by direct contact and oxidation stress on glutathione, which serve as a redox mediator in bacteria [7].…”
Section: Discussionmentioning
confidence: 99%
“…The factors influence to antibacterial effect come the medium culture condition (Mueller-Hinton Broth) or the purity of GO [55]. In contrast, other reports showed that GO had a bactericidal effect [10,56]. Previously, a three-step antibacterial mechanism of graphene-based materials was proposed: initial cell deposition, membrane stress caused by direct contact and oxidation stress on glutathione, which serve as a redox mediator in bacteria [7].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, the CDs, including carbon quantum dots (CQDs; sp 2 /sp 3 carbon) and graphene quantum dots (GQDs; sp 2 carbon), can be functionalized with different molecules or other functional groups for labelling, sensing, tissue imaging, and antibacterial applications. 20 Hence, the determination of the functional groups of the CDs is very important for the following applications. In this research, the functional groups of the negative-charge CDs were measured by using the FT-IR instrument and the data was as shown in Fig.…”
Section: Characterization Of the Cdsmentioning
confidence: 99%
“…Compared with reported nanomaterials, carbon nanomaterials (e.g. fullerenes, carbon nanotubes, graphenes, carbon quantum dots) with broad spectral coverage and other superior material properties have attracted wider attention in antibacterial and related applications in recent years [8][9][10] . Carbon quantum dots (CQDs), especially hetero-element doped CQDs with particle size of less than 10 nm, stand out in the eld of antibacterial research due to their advantageous properties including nontoxic nature, photostability, versatility in surface functionality for desired microbial adhesion and interactions, and their production from abundant and inexpensive precursors for extremely broad and low to ultralow cost applications [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%